Adaptive Law For Inclusivity : Regulatory Reform Sports Education for The bearer Disability in the Perspective of Human Rights Man - Gevan Naufal Wala; Anindya Nikeisha Wala (Siber International Journal of Sport Education, 2024)
This research aims to analyze the reform of educational sports regulations for persons with disabilities in Indonesia from a human rights perspective. Through normative legal research with a socio-legal approach, the study examines the gap between international legal frameworks and national regulations regarding inclusivity in educational sports. The results show that educational sports regulations in Indonesia have not fully accommodated the principles of reasonable accommodation and universal design as mandated by the UN Convention on the Rights of Persons with Disabilities. An adaptive law model that integrates human rights perspectives, participation of persons with disabilities in policy-making, and learning from international best practices is recommended as a reform framework. The development of adaptive and inclusive regulations must prioritize accessibility, availability, and quality of educational sports services as a form of fulfilling the rights of persons with disabilities in education and social participation.